A Gd-Nb co-doped perovskite and its preparation method and application

Through the SPS sintering method and annealing and carbon removal treatment, the problems of long synthesis cycle and low density of perovskite zircon solidified bodies were solved, and the rapid preparation and high density of Gd-Nb co-doped perovskite zircon ceramic solidified bodies were achieved. Suitable for solidification of high-level nuclear waste.

CN118515479BActive Publication Date: 2025-01-24SOUTHWEAT UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410576802.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-01-24
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The prior art has problems of long synthesis cycle and low density when synthesizing perovskite zircon cured bodies at high temperatures, which affects the stability of nuclides in cured substrates.

Method used

The discharge plasma sintering method (SPS) is used to prepare the GD-NB mixed with perovskite vermiculite ceramic curing body, sintering by single-axis pressure at 1100-1250 ° C, and then annealing carbon removal to increase density.

Benefits of technology

It has significantly shortened the preparation time, increased the density of the GD-NB mixed with perovskite vermiculite ceramics, and enhanced its collaborative processing capabilities to the GD and fission element NB of the nuclein.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515479B_ABST
    Figure CN118515479B_ABST
Patent Text Reader

Abstract

The invention discloses a Gd-Nb co-doped perovskite and a preparation method and application thereof, and belongs to the technical field of solidification of highly radioactive nuclear waste. The preparation method of the Gd-Nb co-doped perovskite in the present invention comprises the following steps: grinding and mixing a calcium source, a zirconium source, a titanium source, a gadolinium source, a niobium source, and an oxygen source, performing SPS sintering at 1100-1250°C, and performing annealing and decarbonization after sintering to obtain the Gd-Nb co-doped perovskite. The present invention synergistically processes the actinide nuclide substitute Gd and the fission element Nb, has a short synthesis cycle, and the prepared Gd-Nb co-doped perovskite has a high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solidification of highly radioactive nuclear waste, and more specifically to a Gd-Nb co-doped perovskite and a preparation method and application thereof. Background Art

[0002] Radioactive waste is inevitably generated in the process of nuclear energy utilization. Among them, high-level radioactive waste (HLW) has the characteristics of long half-life and high toxicity, which will pose a huge threat to the ecological environment and human life and health. How to dispose of HLW safely and effectively in the long term has become an urgent issue. At present, deep geological disposal is a solution widely recognized by various countries. Among them, solidification treatment is the most core link in deep geological disposal. Since the solidified body is in an extreme environment, strict requirements are placed on the solidified body substrate.

[0003] Perovskite (chemical formula: ABC2O7) is a fluorite derivative among ceramic-based materials. It has the advantages of high inclusion rate of actinide nuclides and good chemical stability and radiation stability. It is considered to be one of the ideal solidification substrates for HLW. It is worth noting that in addition to the highly toxic actinide nuclides, HLW also includes 95 Nb and other radioactive fission fragment nuclides. Due to the high cost of radioactive nuclide separation, complex chemical decontamination process, and large amount of secondary waste liquid, based on the above considerations, when perovskite zircon solidifies HLW, the synergistic treatment of actinide nuclides and fission element Nb has great practical significance. Since actinide nuclides are extremely radioactive, researchers usually use lanthanide elements as substitutes for actinide nuclides for related research.

[0004] At present, the main problems of traditional high-temperature synthesized perovskite solid ceramics are long synthesis cycle (about 72h) and low density of synthesized samples, which will greatly affect the stability of nuclides in the solidified matrix. So far, there is still no preparation method for co-doping perovskite with actinide nuclides substitutes and fissile element Nb that can shorten the synthesis cycle and improve the density. Summary of the invention

[0005] In view of the above problems, the present invention provides a Gd-Nb co-doped perovskite and a preparation method and application thereof. The present invention synergistically processes the actinide nuclide substitute Gd and the fission element Nb, and the synthesis cycle is short. The prepared Gd-Nb co-doped perovskite has high density.

[0006] The first object of the present invention is to provide a method for preparing Gd-Nb co-doped perovskite, comprising the following steps:

[0007] The calcium source, zirconium source, titanium source, gadolinium source, niobium source and oxygen source are ground and mixed, and then SPS sintered at 1100-1250°C. After sintering, annealing and decarbonization are performed to obtain Gd-Nb co-doped perovskite.

[0008] Further preferably, during SPS sintering, the pressure is 25-40 MPa and the holding time is 30-40 min.

[0009] Further preferably, during SPS sintering, the temperature is 1150° C., the pressure is 25 MPa, and the holding time is 30 min.

[0010] Further preferably, the temperature of annealing and decarburization is 600-1000° C., and the annealing time is 2-3 hours.

[0011] Further preferably, the temperature of annealing and decarburization is 900° C. and the annealing time is 2 h.

[0012] Further preferably, the calcium source is CaCO3, and the zirconium source, titanium source, gadolinium source, and niobium source are all oxides containing corresponding elements;

[0013] The oxygen source is provided by the oxygen in the calcium source, zirconium source, titanium source, gadolinium source and niobium source containing the corresponding elements.

[0014] More preferably, the molar ratio of the calcium source, zirconium source, titanium source, gadolinium source and niobium source is 0.95-1.05:0.85-0.95:1.85-1.95:0.05-0.15; the molar ratio of the gadolinium source and the niobium source is 1:1.

[0015] More preferably, the molar ratio of the calcium source, the zirconium source, the titanium source, the gadolinium source, and the niobium source is 1:0.9:1.9:0.1:0.1.

[0016] The second object of the present invention is to provide Gd-Nb co-doped perovskite prepared by the above preparation method.

[0017] The third object of the present invention is to provide the use of the above-mentioned Gd-Nb co-doped perovskite in solidifying high-level nuclear waste.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention adopts spark plasma sintering to prepare Gd-Nb co-doped perovskite ceramic solid body, applies uniaxial pressure during the sintering process to increase the density of the sample. The present invention realizes the synergistic treatment of actinide nuclide substitute Gd and fission fragment nuclide Nb in the perovskite ceramic solid body.

[0020] (2) The present invention greatly shortens the time for preparing Gd-Nb co-doped perovskite ceramic solid bodies, improves production efficiency, and provides a solution for the engineering application of perovskite ceramic solid bodies. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1The XRD patterns of the Gd-Nb co-doped perovskite solid bodies prepared in the examples and comparative examples of the present invention before annealing;

[0022] Figure 2 The images are of samples before annealing (a) and after annealing (b) in Example 5 of the present invention;

[0023] Figure 3 The XRD patterns of the annealed sample in Example 5 of the present invention and the Gd-Nb co-doped perovskite solid body sintered at a conventional high temperature in Comparative Example 1;

[0024] Figure 4 Density diagram of the Gd-Nb co-doped perovskite ceramic solid body prepared in Example 5 of the present invention and the Gd-Nb co-doped perovskite ceramic solid body sintered at a conventional high temperature in Comparative Example 1;

[0025] Figure 5 These are scanning electron microscope images of the conventional high temperature sintered Gd-Nb co-doped perovskite solid body (a) in Comparative Example 1 of the present invention and the Gd-Nb co-doped perovskite ceramic solid body (b) prepared in Example 5. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Chinese invention patent CN111004032A provides a method for preparing perovskite by vacuum discharge plasma (SPS), which prepares pure CaZrTi2O7, while the present invention is to prepare a Gd-Nb-doped perovskite solid body. Due to the change in composition, the formation enthalpy is different. At the same time, Nb is easy to react with graphite at high temperature to form compounds such as NbC, which can easily lead to the synthesis of Gd-Nb-doped perovskite under unsuitable conditions. The impurity composition is diverse and complex, and the sample is easy to break into fine particles or a large number of fragments of different sizes during annealing. Therefore, the present invention provides a preparation method of Gd-Nb co-doped perovskite, and the specific technical scheme is as follows:

[0028] A method for preparing Gd-Nb co-doped perovskite comprises the following steps:

[0029] The calcium source, zirconium source, titanium source, gadolinium source, niobium source and oxygen source are ground and mixed, and then SPS sintered at 1100-1300° C. After sintering, annealing and decarbonization are performed to obtain Gd-Nb co-doped perovskite.

[0030] In the preparation process, the present invention uses CaZrTi2O7 as a matrix and successfully introduces Gd and Nb by SPS sintering, Gd is introduced into the Zr position, and Nb is introduced into the Ti position. The present invention realizes the coordinated treatment of the actinide nuclide substitute Gd and the fission fragment nuclide Nb.

[0031] It should be noted that in the present invention, the raw materials are used to provide metal and O sources and cannot be replaced at will. Using other raw materials will make the reaction difficult or introduce various impurities.

[0032] In a preferred embodiment of the present invention, the calcium source is CaCO3, and the zirconium source, titanium source, gadolinium source, and niobium source are all oxides containing corresponding elements;

[0033] The oxygen source is provided by the oxygen in the calcium source, zirconium source, titanium source, gadolinium source and niobium source containing the corresponding elements.

[0034] Specifically, the zirconium source, titanium source, gadolinium source and niobium source are ZrO2, TiO2, Gd2O3 and Nb2O5 respectively.

[0035] In a preferred embodiment of the present invention, the molar ratio of the calcium source, zirconium source, titanium source, gadolinium source and niobium source is 0.95-1.05:0.85-0.95:1.85-1.95:0.05-0.15; the molar ratio of the gadolinium source and the niobium source is 1:1.

[0036] More preferably, the molar ratio of the calcium source, the zirconium source, the titanium source, the gadolinium source, and the niobium source is 1:0.9:1.9:0.1:0.1.

[0037] In a preferred embodiment of the present invention, during SPS sintering, the pressure is 25-40 MPa and the holding time is 30-40 min.

[0038] It should be noted that changes in sintering temperature and pressure will affect the reaction efficiency of the raw materials, and applying pressure can increase the density of the sample. Further preferably, the optimal temperature is 1150°C, the pressure is 25 MPa, and the annealing temperature is 900°C.

[0039] In a preferred embodiment of the present invention, the temperature for annealing to remove carbon and stress is 600-1000° C., and the annealing time is 2-3 hours.

[0040] It should be noted that the role of annealing is to remove C and residual stress in the sample. Carbon removal is to prevent carbon from generating uncontrollable factors during the solidification process, which may lead to rapid failure of the solidification body. This is because carbon can react with other substances under water-heat-acid-base conditions. Further preferred, the optimal temperature is 900°C and the annealing time is 2h.

[0041] It is difficult to synthesize Gd-Nb doped perovskite under unsuitable conditions. The impurity composition is diverse and complex, and the sample is easily broken into fine particles or a large number of fragments of varying sizes during annealing. Based on this, the present invention studies the Gd-Nb doped perovskite prepared under different parameters.

[0042] The present invention is further described below by examples and comparative examples:

[0043] Example 1

[0044] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0045] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0046] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0047] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat it to 650°C at a heating rate of 130°C / min, then heat it to 1200°C at a heating rate of 50°C / min, the sintering pressure is 40MPa, and the sintering is completed after keeping warm for 30min, then cool it to 650°C at a rate of 50°C / min, and then cool it with the furnace to obtain the SPS sintered sample;

[0048] The sample prepared by the present invention was broken into 4 pieces after demoulding, and no annealing treatment was performed.

[0049] Example 2

[0050] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0051] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0052] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0053] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat it to 650°C at a heating rate of 130°C / min, then heat it to 1200°C at a heating rate of 50°C / min, the sintering pressure is 30MPa, and the sintering is completed after 30 minutes of heat preservation, and then cool it to 650°C at a rate of 50°C / min, and then cool it with the furnace to obtain the SPS sintered sample;

[0054] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 900°C for 2 hours to remove carbon and stress to obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0055] The sample prepared by the present invention is broken into three pieces after demoulding, and the degree of fragmentation of the sample after annealing is consistent with that before annealing.

[0056] Example 3

[0057] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0058] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0059] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0060] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into an SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, then heat the temperature to 1200°C at a heating rate of 50°C / min, the sintering pressure is 25MPa, and the sintering is completed after 30 minutes of heat preservation, then cool to 650°C at a rate of 50°C / min, and then cool with the furnace to obtain an SPS sintered sample;

[0061] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 900°C for 2 hours to remove carbon and stress to obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0062] The sample prepared in this example was broken into three pieces after demoulding, and the degree of fragmentation of the sample after annealing was consistent with that before annealing.

[0063] Example 4

[0064] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0065] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0066] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0067] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1150°C at a heating rate of 50°C / min. The sintering pressure is 30MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled with the furnace to obtain the SPS sintered sample;

[0068] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 900°C for 2 hours to remove carbon and stress to obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0069] The sample prepared in this example was intact without cracks after demoulding, and the carbon infiltrated into the sample was completely removed after annealing, but slight cracks occurred on the surface of the sample at the annealing temperature.

[0070] Example 5

[0071] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0072] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0073] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0074] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1150°C at a heating rate of 50°C / min. The sintering pressure is 25MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled with the furnace to obtain the SPS sintered sample;

[0075] Step 5: Annealing treatment: Place the SPS sintered samples in a muffle furnace and anneal them at 900°C for 2h to remove carbon and obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0076] The sample prepared in this embodiment was intact without cracks after demoulding, and the carbon infiltrated into the sample was completely removed after annealing. The sample did not break at this annealing temperature. Among them, annealing at 600-800℃ failed to completely remove carbon, so 900℃ was selected.

[0077] Example 6

[0078] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 0.95:0.95:1.85:0.15:0.15.

[0079] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0080] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0081] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1150°C at a heating rate of 50°C / min. The sintering pressure is 25MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled with the furnace to obtain the SPS sintered sample;

[0082] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 1000°C for 2.5h to remove carbon and obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0083] Example 7

[0084] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1.05:0.85:1.95:0.05:0.05.

[0085] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0086] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0087] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1150°C at a heating rate of 50°C / min. The sintering pressure is 25MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled with the furnace to obtain the SPS sintered sample;

[0088] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 600°C for 3 hours to remove carbon and obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0089] Comparative Example 1

[0090] A conventional high temperature preparation method of Gd-Nb co-doped perovskite ceramics comprises the following steps:

[0091] Step 1. Ingredients: Weigh the raw materials of CaCO3, ZrO2, TiO2, Gd2O3 and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0092] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0093] Step 3, sample preparation: Take 1 g of the uniformly mixed powder and put it into a circular tableting mold with a diameter of 10 mm, and press it into pellets under a uniaxial pressure of about 400 MPa under a manual press.

[0094] Step 4: First sintering of Gd-Nb co-doped perovskite ceramics: placing the pressed pellets in a muffle furnace and sintering at 1500° C. for 48 hours;

[0095] Step 5: Ball milling of Gd-Nb co-doped perovskite ceramics: placing the first sintered Gd-Nb co-doped perovskite ceramics into a ball mill, and ball milling at a speed of 1500 rpm for 30 min to a fine powder;

[0096] Step 6. Sample preparation: Take 1 g of the mixed powder after ball milling and put it into a circular tableting mold with a diameter of 10 mm, and press it into pellets under a uniaxial pressure of about 400 MPa under a manual press.

[0097] Step 7. Second sintering of Gd-Nb co-doped peroximate zircon ceramics: Place the pressed pellets into a muffle furnace and sinter at 1500° C. for 48 hours to obtain Gd-Nb co-doped peroximate zircon ceramics.

[0098] Comparative Example 2

[0099] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0100] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0101] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0102] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into an SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat the temperature to 1300°C at a heating rate of 50°C / min, with a sintering pressure of 30MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled in the furnace to obtain an SPS sintered sample;

[0103] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 1000°C for 2 hours to remove carbon and stress, thereby obtaining a Gd-Nb co-doped perovskite ceramic solid body.

[0104] The sample prepared by sintering in step 4 of this comparative example was broken into unusable small fragments after demoulding, and the sample was further broken into even finer particles after annealing.

[0105] Comparative Example 3

[0106] Step 1. Ingredients: Weigh CaCO3, ZrO2, TiO2, Gd2O3, Nb2O5 and other raw materials according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0107] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0108] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0109] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1250°C at a heating rate of 50°C / min. The sintering pressure is 50MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled with the furnace to obtain the SPS sintered sample;

[0110] The sample prepared in step 4 of this comparative example broke into unusable fine granular fragments after demoulding, which may be due to the excessively high carburizing ratio. Therefore, no annealing treatment was performed.

[0111] Comparative Example 4

[0112] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0113] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0114] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0115] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1250°C at a heating rate of 50°C / min. The sintering pressure is 30MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then cooled in the furnace to obtain the SPS sintered sample;

[0116] The sample prepared in step 4 of this comparative example broke into unusable small pieces after demoulding, and no annealing treatment was performed.

[0117] Comparative Example 5

[0118] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0119] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0120] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0121] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into an SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, then heat it to 1200°C at a heating rate of 50°C / min, the sintering pressure is 50MPa, and the sintering is completed after keeping the temperature for 30 minutes, then cool it to 650°C at a rate of 50°C / min, and then cool it with the furnace to obtain an SPS sintered sample;

[0122] The sample prepared in step 4 of this comparative example broke into unusable small pieces after demoulding, and therefore, no annealing treatment was performed.

[0123] Comparative Example 6

[0124] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0125] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0126] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0127] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1150°C at a heating rate of 50°C / min. The sintering pressure is 40MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then the SPS sintered sample is obtained by cooling with the furnace;

[0128] The sample prepared in this comparative example broke into 8 pieces after demoulding, and was judged not to meet the requirements, so no annealing treatment was performed.

[0129] Comparative Example 7

[0130] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0131] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0132] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0133] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into an SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, then heat the temperature to 1100°C at a heating rate of 50°C / min, the sintering pressure is 30MPa, and the sintering is completed after 30 minutes of heat preservation, then cool to 650°C at a rate of 50°C / min, and then cool with the furnace to obtain an SPS sintered sample;

[0134] The sample prepared in step 4 of this comparative example was broken into 7 pieces without annealing treatment.

[0135] Comparative Example 8

[0136] Step 1. Ingredients: Weigh the raw materials CaCO3, ZrO2, TiO2, Gd2O3, and Nb2O5 according to the molar ratio of 1:0.9:1.9:0.1:0.1.

[0137] Step 2, grinding: put the raw materials weighed according to the stoichiometric ratio into a mortar, add anhydrous ethanol medium, and grind with an agate rod for 30 minutes until dry and without color difference to obtain a uniform mixed powder;

[0138] Step 3: Sample preparation: Evenly spread graphite paper inside a 30mm diameter graphite mold to prevent the sample from sticking to the mold. Take 5g of the evenly mixed powder and put it into the graphite mold.

[0139] Step 4, SPS sintering of Gd-Nb co-doped perovskite ceramics: Place the mold containing the mixed powder into the SPS sintering furnace, heat the temperature to 650°C at a heating rate of 130°C / min, and then heat it to 1250°C at a heating rate of 50°C / min. The sintering pressure is 25MPa. After 30 minutes of heat preservation, the sintering is completed, and then the temperature is reduced to 650°C at a rate of 50°C / min, and then the SPS sintered sample is obtained by cooling with the furnace;

[0140] Step 5: Annealing: Place the SPS sintered sample in a muffle furnace and anneal it at 900°C for 2 hours to remove carbon and stress to obtain a Gd-Nb co-doped perovskite ceramic solid body.

[0141] The sample prepared in this comparative example was broken into 6 pieces after demoulding, and the degree of fragmentation of the sample after annealing was consistent with that before annealing.

[0142] Figure 1 The XRD diagrams of the unannealed and decarbonized samples of Examples 1-7 and Comparative Examples 2-8 and Comparative Example 1 show that the main phase of the synthesized samples is monoclinic perovskite and the trace phase is perovskite. There is an obvious carbon peak at about 27°, which is caused by the migration of carbon elements in the carbon paper under high temperature and high pressure.

[0143] For the samples prepared in the examples and comparative examples of the present invention, the samples of Examples 1-4 and Comparative Examples 2-5 were broken because the carbon element in the carbon paper penetrated into the samples under high temperature and high pressure during the sintering process, wherein the samples of Comparative Examples 2-5 were broken into unusable small fragments, and the sample of Comparative Example 6 was broken into 8 pieces, which did not meet the use requirements. The sample of Comparative Example 7 was broken because the temperature under the sintering conditions could not make the sample completely synthesized. The sample of Comparative Example 8 was broken into 6 pieces, which did not meet the use requirements.

[0144] The samples of Examples 1-3 had a small degree of fragmentation. However, the fragmentation of the samples would affect the curing performance of Gd-Nb co-doped perovskite. The sample of Example 4 had fragmentation on the surface of the sample due to stress after annealing. The sample prepared in Example 5 was intact and crack-free after demoulding.

[0145] The performance of the samples prepared in Examples 6 and 7 is similar to that of the sample in Example 5, and Example 5 is used for specific description below.

[0146] Figure 2The sample diagrams before and after annealing of Example 5 show that the sample is intact and has no cracks, indicating that the sintering parameters described in this example are feasible. During the sintering process, as the temperature and pressure decrease, the degree of fragmentation of the sintered sample decreases. During the preparation process, it is hoped that the sintered sample is intact and has no cracks, because in an actual underground disposal repository, if the sample is in a fragmented state, the contact area with water will increase, which will lead to an increase in the leaching rate of nuclides fixed in the ceramic. Therefore, the smaller the degree of fragmentation of the sintered sample, the better.

[0147] Figure 3 The XRD diagram of the sample of Example 5 after annealing to remove carbon and stress and that of Comparative Example 1. Almost all peaks in the XRD spectrum can correspond to monoclinic perovskite, and the weak peak around 33° can be attributed to the perovskite phase. No carbon peak at 26° was observed, indicating that carbon was removed at an annealing temperature of 900°C.

[0148] Figure 4 This is a density diagram of the samples of Example 5 and Comparative Example 1. It can be seen from the figure that the density of the Gd-Nb co-doped peroxicam ceramic solid body prepared by SPS used in Example 5 is significantly greater than that of the sample prepared by traditional high temperature in the comparative example, indicating that the sample under the SPS synthesis conditions has good density.

[0149] Figure 5 The SEM images of the sample of Example 5 after annealing (b) and the sample of Comparative Example 1 (a) show that many holes exist on the surface of the sample sintered by the conventional method. The grains of the sample sintered by SPS are closely arranged and the porosity is relatively low.

[0150] This is similar to Figure 4 Corresponding to the density result, the higher the density of the sample, the better the density, the fewer internal pores, which can reduce the area with the leaching solution and reduce the leaching rate.

[0151] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0152] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing Gd-Nb co-doped perovskite, characterized in that: The following steps are involved: The calcium source, zirconium source, titanium source, gadolinium source, niobium source and oxygen source are ground and mixed, and then SPS sintered at 1150°C. After sintering, annealing and decarburization are performed to obtain Gd-Nb co-doped perovskite; during SPS sintering, the pressure is 25MPa and the holding time is 30min; the annealing and decarburization temperature is 900°C and the annealing time is 2h; the molar ratio of the calcium source, zirconium source, titanium source, gadolinium source and niobium source is 1:0.9:1.9:0.1:0.

1.

2. The method for preparing a Gd-Nb co-doped perovskite according to claim 1, characterized in that: The calcium source is CaCO3, and the zirconium source, titanium source, gadolinium source, and niobium source are all oxides containing corresponding elements; The oxygen source is provided by the oxygen in the calcium source, zirconium source, titanium source, gadolinium source and niobium source containing the corresponding elements.

3. A Gd-Nb co-doped perovskite prepared by the preparation method according to any one of claims 1 to 2.

4. Use of the Gd-Nb co-doped perovskite according to claim 3 in solidifying high-level nuclear waste.

Citation Information

Patent Citations

  • Zircon perovskite type ceramic solidified body as well as preparation method and application thereof

    CN111004032A